2018
DOI: 10.1002/ncp.10021
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Tumor Seeding at the Percutaneous Endoscopic Gastrostomy Site

Abstract: The National Institutes of Health National Cancer Institute estimates that over 13,000 new cases of head and neck cancer (HNC) will be diagnosed in 2017. Patients with HNC often require enteral nutrition (EN) via gastrostomy tube to provide nutrition support and hydration because of tumor obstruction of the oropharynx and/or cumulative effects of chemoradiation therapy. The percutaneous endoscopic gastrostomy (PEG) tube has become the preferred technique for EN access because placement is considered a minimall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…The possibility of metastasis should always be taken into consideration in patients with HNC that present with skin changes at the gastrostomy site, which requires confirmation by biopsy. ( 8 ) The risks of tumor implantation in the abdominal wall are higher in patients of advanced age and/or advanced tumor staging. ( 6 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of metastasis should always be taken into consideration in patients with HNC that present with skin changes at the gastrostomy site, which requires confirmation by biopsy. ( 8 ) The risks of tumor implantation in the abdominal wall are higher in patients of advanced age and/or advanced tumor staging. ( 6 )…”
Section: Discussionmentioning
confidence: 99%
“…A possibilidade de metástase deve sempre ser considerada em pacientes com CCP que apresentem alterações dermatológicas no sítio da gastrostomia, necessitando ser confirmadas com biópsia. ( 8 ) Os riscos de implantação tumoral na parede abdominal são maiores em pacientes de idade avançada e/ou estadiamento tumoral avançado. ( 6 )…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Actually, patients with proximal GI cancers are at risk of seeding from the primary tumour site to the PEG tract by mechanical transfer. In 1989, Preyer and Thul [24] reported the first patient with PEG tract metastasis, and since then, new cases have been identified annually [24][25][26][27]. In a recent prospective controlled study involving 50 patients, positive cytology for malignant cells was described in 22.5% of the stomas immediately after PEG placement using the pull method, and after 3-6 months of follow-up, persistence of these cells was detected in 9%.…”
Section: Nasal Tubesmentioning
confidence: 99%
“…Although some cases of favourable evolution have been reported, this adverse event is often associated with a poor oncologic outcome [24,26,29]. Thus, the use of a direct gastric puncture technique for percutaneous feeding tube placement in patients with proximal GI cancer has been recommended by several authors, especially in patients receiving radical therapy with curative intent [20,25]. Comparative studies have shown similar complication rates, except for a more common occurrence of delayed tube disfunction and minor bleeding episodes with the introducer approach [30,31].…”
Section: Nasal Tubesmentioning
confidence: 99%